+0  
 
0
200
2
avatar
Guest Apr 2, 2015

Best Answer 

 #1
avatar+17705 
+5

f(x + 1)  =  x2 - 3x + 2   --->   f(x + 1)  =  (x - 2)(x - 1)   --->   f(x)  =  (x - 3)(x - 2)

f(x)  =  0   --->   (x - 3)(x - 2)  =  0   --->   x  =  2  or  x  =  3

Sum  =  2 + 3  =  5 

geno3141  Apr 2, 2015
Sort: 

2+0 Answers

 #1
avatar+17705 
+5
Best Answer

f(x + 1)  =  x2 - 3x + 2   --->   f(x + 1)  =  (x - 2)(x - 1)   --->   f(x)  =  (x - 3)(x - 2)

f(x)  =  0   --->   (x - 3)(x - 2)  =  0   --->   x  =  2  or  x  =  3

Sum  =  2 + 3  =  5 

geno3141  Apr 2, 2015
 #2
avatar+91432 
0

That is another really tricky little question.

thanks Geno :)

Melody  Apr 3, 2015

7 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details